Lower intracellular hydrogen peroxide levels in cells overexpressing CuZn-superoxide dismutase - Teixeira, Henrique D. (The National Academy of Sciences, 1998)
Transfection of V79 Chinese hamster cells produced clones in which CuZn-superoxide dismutase (CuZn-SOD) activities were 2.2- to 3.5-fold higher than in the parental cells. An overall reduction of antioxidant enzyme activities and both total and oxidized glutathione levels had been found in these clones. Aconitase activities in these cells were determined to indirectly measure the O(2)(−) steady-state levels. As expected, in cells overexpressing CuZn-SOD, both total and cytosolic aconitase activities have increased. Because these clones showed reduced oxidized glutathione contents, it is unlikely that they present higher H(2)O(2) steady-state levels as a consequence of the higher SOD levels. This was confirmed by measuring H(2)O(2) steady-state levels in cells by flow cytometric analysis of 2′,7′-dichlorofluorescein diacetate-treated cells. Despite the decreased antioxidant defenses, three of the clones overexpressing CuZn-SOD showed reduced H(2)O(2) steady-state levels. These reduced H(2)O(2) steady-state levels were found even when the cells were treated with the O(2)(−) generator 2,3-dimethoxy-1,4-naphthoquinone. These data provide in vivo support for the hypothesis proposed by Liochev and Fridovich [Liochev, S. I. & Fridovich, I. (1994) Free Radical Biol. Med. 16, 29–33] that O(2)(−) dismutation prevents the formation of higher H(2)O(2) levels by other reactions.